The Effect of Distraction Therapy (Pray) to The Surgical Pain Intensity Among Post-spinal Anesthesia Patients at Andi Sulthan Daeng Radja Hospital's Recovery Room, Bulukumba Regency of South Sulawesi - Syamsul Hidayat; Yustiana Olfah; Sugeng Sugeng (Journal of Health (JoH), 2016)
Background: The needs of pain free after surgery occurs when analgesic medicine effect is run out. Thus, nursing care with distraction therapy can lead to the reduce of such pain sensation (Prasetyo, 2010). One of independent nursing interventions to relieve patients’ pain is to measure pain scale and then to give further intervention, either relaxation or distraction. Objectives: To identify the effect of distraction therapy, which is pray, to the surgical pain intensity of post-spinal anesthesia patients at Sulthan Daeng Radja hospital’s recovery room, Bulukumba regency of South Sulawesi Methods: A quasi experiment with one group pretest-posttest design was used in this research. The samples group was measured with pretest before being given an intervention and it was being re-measured after the intervention (posttest). Samples were chosen through non-random sampling, which is purposive sampling. Thirty eight samples were involved and being given such distraction therapy throughout the period of August 26th to October 19th 2013. Results: There was a significant result shown by using McNemar-analysis (p value =0.00). This reveals that there were decline in pain intensity after such distraction therapy among such patients. Conclusions: Distraction therapy (praying) reduces surgical pain intensity after spinal anesthesia. Therefore it can be used as an independent nursing intervention among patients hospitalized with pain problems.